2019
DOI: 10.3390/ijms20194907
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D as A Protector of Arterial Health: Potential Role in Peripheral Arterial Disease Formation

Abstract: Atherosclerotic occlusive diseases and aneurysms that affect large and medium-sized arteries outside the cardiac and cerebral circulation are collectively known as peripheral arterial disease (PAD). With a rise in the rate of aging population worldwide, the number of people diagnosed with PAD is rapidly increasing. The micronutrient vitamin D is an important steroid hormone that acts on many crucial cellular mechanisms. Experimental studies suggest that optimal levels of vitamin D have beneficial effects on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 169 publications
0
22
0
4
Order By: Relevance
“…Over the years, several observational studies in adults have found an association between low vitamin D levels and higher blood pressure levels, myocardial infarction, heart failure, coronary heart disease, peripheral arterial disease, and atherosclerosis [21,44,45].…”
Section: Vitamin D Deficiency and Cardiovascular Risk Factorsmentioning
confidence: 99%
“…Over the years, several observational studies in adults have found an association between low vitamin D levels and higher blood pressure levels, myocardial infarction, heart failure, coronary heart disease, peripheral arterial disease, and atherosclerosis [21,44,45].…”
Section: Vitamin D Deficiency and Cardiovascular Risk Factorsmentioning
confidence: 99%
“…VitD has metabolic activity through the VDR receptor whose gene is located on chromosome 12q12-q14 [ 38 ]. VDR binds the active form of VitD (calcitriol), which causes interaction with the retinoid X receptor ( RXR ), thus forming a VDR / RXR /cofactor complex that binds to the elements of the VitD response element ( VDRE ) in the gene's promoter region.…”
Section: Discussionmentioning
confidence: 99%
“…VDR binds the active form of VitD (calcitriol), which causes interaction with the retinoid X receptor ( RXR ), thus forming a VDR / RXR /cofactor complex that binds to the elements of the VitD response element ( VDRE ) in the gene's promoter region. This leads to activation or suppression of expression by interacting with additional coregulators [ 38 40 ]. The VDR protein is expressed in many types of cells in the human organism [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypovitaminosis D has been associated with higher prevalence and severity of PAD disease. The potential mechanism is explained by the fact that hyperparathyroidism increases the risk of osteomalacia and arterial calcification (Krishna, 2019). Folate and vitamin D deficiencies have been linked to an increased risk of PAD and worsening ambulatory sta-tus (Kokkinidis et al, 2020a).…”
Section: Importance Of Dietary Habits and Nutrition In Patients With mentioning
confidence: 99%